Postharvest control of anthracnose in avocado with cassava starch and corn starch films - Soares de Freitas, Aurivan; Maria Gilmara de Oliveira Soares; Vieira Barros, Aline; Leticia da Silveira, Amanda; Sarah Costa Silva, Sarah; Alves, Eduardo (Comunicata Scientiae, 2022)
The objective of this study was to evaluate the effect of cassava starch and corn starch films on the control of anthracnose in avocado. The fruits were inoculated with conidia suspension and were then immersed in solutions with cassava starch and corn starch alone or in combination at concentrations of 1, 2, 3 and 4% under curative and preventive methods. The variables analysed included mean damaged area, area under the disease progress curve (AUDPC) and fruit fresh weight. Under the curative method, the mean damaged area and AUDPC were reduced in fruits treated with 1% and 4% cassava starch and 1% corn starch. Under the preventive method, fruits treated with 2% cassava starch or 2% corn starch alone resulted in reduced mean damaged area and AUDPC. The combinations of cassava starch and corn starch at 2, 3, and 4% were effective in reducing the mean damaged area and AUDPC under curative control. Under the preventive method, the combinations of cassava starch and corn starch at 2 and 3% reduced the AUDPC, and the mean damaged area was decreased with both starches at 3%. Scanning electron microscopy images revealed a layer of protective film on the fruit's surface that probably prevented the pathogen from penetrating. In addition, there was deformation of hyphae promoted by the action of the films.